S37 The response of objectively-measured cough to treatment in tuberculosis: an exploratory study. (12th November 2015) - Turner, RD; Birring, SS; Bothamley, GH
Abstract : Introduction and objective: Cough is predominant in pulmonary tuberculosis and transmits infection, yet it is unclear how rapidly it responds to treatment. We explored changes in objectively-measured cough frequency during TB therapy with respect to other markers of disease. Method: Before or on commencing anti-tuberculous treatment, consecutive patients with pulmonary tuberculosis wore the Leicester Cough Monitor for 24 h, a device comprising a small digital audio recorder and microphone with software for cough detection. Those with a baseline cough frequency greater than the upper limit of normal ( c. 100 coughs/24 h [c/24h]) were asked to undergo repeat monitoring during initial hospitalisation (if applicable), and later to coincide with routine clinic attendance or directly observed therapy (DOT). Results: Median baseline cough frequency was 203 (IQR 75–470) c/24 h in all participants (n = 44), and >100 c/24 h in 32 (73%). 22 patients were willing and available to undergo serial cough monitoring (12 current smokers, 18 sputum smear positive disease [12 also with visible lung cavities], and one with HIV). Three had isoniazid-resistant disease; the remainder were fully drug-sensitive. All were eventually treated successfully. None had other respiratory diagnoses. Cough frequency in the majority declined consistently during therapy with substantial improvements by one week (Figure 1 ). At 2 and/or 8 weeks, five patients had a higher cough frequency than at baseline. Amongst these slow responders there was initial extensive radiographic change (n = 1), poor drug adherence with ongoing weight loss (n = 1), a paradoxical reaction to treatment with the development of a paraspinal abscess (n = 1), and, in the patient with HIV, persistent sputum smear positivity at 8 weeks with minimal radiographic improvement despite DOT and normal plasma rifampicin levels. One other patient had a highly variable cough frequency during the first 8 weeks of treatment. There was no evidence for an effect of isoniazid resistance, cavitary disease, smear status or smoking on early rates of cough resolution, although there was a trend towards relatively higher cough frequencies in smokers than non-smokers at the end of treatment ( p = 0.100). Conclusions: Objective cough frequency measurement is feasible in tuberculosis and could provide a novel biomarker of treatment response.